2011
DOI: 10.1007/s10765-010-0909-3
|View full text |Cite
|
Sign up to set email alerts
|

Equations of State on Demand: Application for Surrogate Fuel Development

Abstract: The NIST ThermoData Engine (TDE) is a large electronic database containing experimental data with detailed descriptions of relevant metadata and uncertainties that incorporates expert-system software to automatically generate dynamically evaluated data and on-demand equations of state. In this study, we demonstrate how the concept of dynamic data evaluation within the NIST TDE can be used to generate equations of state (EOS) on demand, and give an example where the resulting EOS formulations for pure chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 92 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…Even though 2,2,4,4,6,8,8-heptamethylnonane is not found in petroleum-based fuels, it is often used in surrogate development because it is an inexpensive representative of branched alkanes . Surrogate mixture properties can be predicted from correlations used for multicomponent systems or from other modeling approaches such as molecular dynamic simulations, and these approaches can be used to select the components based on weighting factors that have been found to be relevant to combustion systems. , Care must be taken when developing and using correlations because the behavior of systems with many components can be different from systems with a few components. Fuels such as butanol-derived alcohol-to-jet fuel have been shown to have only a few components, while fuels such as HDCD have many components …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though 2,2,4,4,6,8,8-heptamethylnonane is not found in petroleum-based fuels, it is often used in surrogate development because it is an inexpensive representative of branched alkanes . Surrogate mixture properties can be predicted from correlations used for multicomponent systems or from other modeling approaches such as molecular dynamic simulations, and these approaches can be used to select the components based on weighting factors that have been found to be relevant to combustion systems. , Care must be taken when developing and using correlations because the behavior of systems with many components can be different from systems with a few components. Fuels such as butanol-derived alcohol-to-jet fuel have been shown to have only a few components, while fuels such as HDCD have many components …”
Section: Discussionmentioning
confidence: 99%
“…and these approaches can be used to select the components based on weighting factors that have been found to be relevant to combustion systems. 68,80 Care must be taken when developing and using correlations because the behavior of systems with many components can be different from systems with a few components. Fuels such as butanol-derived alcoholto-jet fuel have been shown to have only a few components, while fuels such as HDCD have many components.…”
Section: ■ Summary and Conclusionmentioning
confidence: 99%
“…One way to help in the selection of components for the surrogate is to determine the trends in the physical properties of mixtures as a function of the structure of the molecule. In petroleum and biobased fuel surrogates, the n -alkane category has been represented by nonane, decane, undecane, dodecane, tridecane, tetradecane, pentadecane, and hexadecane, and the cycloalkane category has included methyl-, propyl-, butyl-, pentyl-, hexyl-, and heptylcyclohexanes. ,, The importance of cycloalkanes in surrogates was explored by Dooley et al, who found that having a cycloalkane in the surrogate mixture accelerated its reactivity to a value that was closer to the reactivity exhibited by fuel for which it was designed. The thermophysical properties of density and viscosity, which are important for the physical processes involved in pumping and droplet formation in an engine, have been measured for binary mixtures of n -dodecane or n -hexadecane with various n -alkylcyclohexanes and of methyl- or butylcyclohexane with various n -alkanes. Because information is lacking for measurements of these properties for n -tridecane mixtures, the goal of this study was to measure the density, viscosity, and speed of sound of mixtures of various n -alkylcyclohexanes in n -tridecane and to place these measurements in the context of mixtures of these cycloalkanes with n -dodecane and n -hexadecane.…”
Section: Introductionmentioning
confidence: 99%
“…TDE is a combination of SOURCE with expert-system software, designed to automatically generate recommended data based on available experimental data and prediction methods, thus providing the ability to produce critically evaluated data dynamically. Dynamic data evaluation, in turn, is one of the central elements of emerging global communication systems in thermodynamics [10][11][12] and is gaining acceptance in facilitating advances in scientific and industrial research [13,14], as well as in the global data validation process, currently involving five major journals in the field [15,16]. Over the years [1][2][3], SOURCE and its underlying data model have evolved from a flat-file system to a non-relational, and, finally, a relational database.…”
Section: Introductionmentioning
confidence: 99%